Canakinumab treatment for patients with active recurrent or chronic TNF receptor-associated periodic syndrome (TRAPS): an open-label, phase II study. Issue 1 (7th June 2016) - Gattorno, Marco; Obici, Laura; Cattalini, Marco; Tormey, Vincent; Abrams, Ken; Davis, Nicole; Speziale, Antonio; Bhansali, Suraj G; Martini, Alberto; Lachmann, Helen J
Abstract : Objective: To evaluate the efficacy of canakinumab, a high-affinity human monoclonal anti-interleukin-1β antibody, in inducing complete or almost complete responses in patients with active tumour necrosis factor receptor-associated periodic syndrome (TRAPS). Methods: Twenty patients (aged 7–78 years) with active recurrent or chronic TRAPS were treated with canakinumab 150 mg every 4 weeks for 4 months (2 mg/kg for those ≤40 kg) in this open-label, proof-of-concept, phase II study. Canakinumab was then withdrawn for up to 5 months, with reintroduction on relapse, and 4 weekly administration (subsequently increased to every 8 weeks) for 24 months. The primary efficacy variable was the proportion of patients achieving complete or almost complete response at day 15, defined as clinical remission (Physician's Global Assessment score ≤1) and full or partial serological remission. Results: Nineteen patients (19/20, 95%; 95% CI 75.1% to 99.9%) achieved the primary efficacy variable. Responses to canakinumab occurred rapidly; median time to clinical remission 4 days (95% CI 3 to 8 days). All patients relapsed after canakinumab was withdrawn; median time to relapse 91.5 days (95% CI 65 to 117 days). On reintroduction of canakinumab, clinical and serological responses were similar to those seen during the first phase, and were sustained throughout treatment. Canakinumab was well tolerated and clinical responses were accompanied by rapid and sustained improvement in health-related quality of life. Weight normalised pharmacokinetics of canakinumab, although limited, appeared to be consistent with historical canakinumab data. Conclusions: Canakinumab induces rapid disease control in patients with active TRAPS, and clinical benefits are sustained during long-term treatment. Trial registration number: NCT01242813; Results.